Analysis Of Theories Of Multicultural Education Approaches in The Context Of Islamic Religious Education - Ishak Ishak; St Wardah Hanafie Das (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This study aims to analyze the theories of multicultural education approach and its application in the context of Islamic Religious Education (PAI). Using a qualitative approach based on literature study, this research explores theories such as social justice, pluralism, social interaction, constructivism, humanism, and social transformation, and their relevance to Islamic values. The results show that multicultural education is in line with Islamic teachings, such as tolerance, justice, empathy, and respect for diversity. The integration of these theories in PAI can create an inclusive learning environment that encourages intercultural dialogue, character development, and respect for differences. Implementation challenges include stereotypes, limited resources and lack of teacher training, while opportunities include increased tolerance, curriculum enrichment and technology utilization. This research highlights the importance of education policies that support multicultural inclusivity and relevance in building a harmonious society.